Effect of Aromatherapy Massage on Anxiety among Patients Undergoing Percutaneous Coronary Intervention - nasrin meshgin abadi; farhad ramezanibadr; khalil mahmoodi (Zanjan University of Medical Sciences and Health Services, 2012)
Background and Objective: Percutaneous Coronary Intervention (PCI) is a common procedure in treatment of coronary artery diseases. Anxiety is a common psychological reaction to cardiovascular interventions. Anxiety can affect physiological responses and cause blood pressure increase, cardiac output decrease, cardiac o2 demand increase, and finally ischemic pain. The aim of this study was to assess the effect of aromatherapy massage on anxiety of patients undergone the PCI. Materials and Methods: In this semi-experimental study, 76 patients undergone elective PCI who had met the inclusion criteria for the study were recruited using convenience sampling method and were randomly divided into two control and experimental groups. The patients in the control group received routine care with eight hours bed rest after the PCI. The patients in the experimental group underwent aromatherapy massage with a solution composed of mint, celery and lavender essences in sweet almond oil )%1 concentration). The intensity of anxiety was measured using the Spilberger state anxiety inventory in three stages (prior to the intervention, immediately after the intervention, and two hours after the intervention) .The incidence of bleeding was observed before and after the intervention. The incidence of hematoma was observed 24 hours after the intervention. Results: The intensity of anxiety had significantly decreased after aromatherapy massage in the experimental group in comparison with the control group (P< 0.0005). The effect was stable up to two hours after the intervention (P< 0.0005). In the experimental group, anxiety decreased significantly after the intervention (P< 0.0005). None of the patients in the study had bleeding. Moreover, 92.1% of patients were satisfied from the intervention procedure. Conclusion: The results showed that the aromatherapy massage was a safe, non-expensive, and effective method in decreasing anxiety of patients undergone the PCI.